Preparation of a B-doped porous g-C3N4 catalyst and a water treatment method based on the catalyst

By preparing B-doped porous g-C3N4 catalyst and applying it to photocatalytic Fenton water treatment, the problems of low H2O2 yield and insufficient pollutant enrichment in the prior art are solved, efficient pollutant degradation and TOC removal are achieved, and the catalyst preparation is simple and environmentally friendly.

CN116196960BActive Publication Date: 2025-03-18JIANGNAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310064626.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2025-03-18
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

The current photocatalytic H2O2 production is low in Fenton technology, resulting in insufficient OH generation and lack of enrichment of pollutants, making it impossible to effectively utilize the generated OH and photogenerated holes.

Method used

通过前驱体自组装后煅烧制备B掺杂多孔g-C3N4催化剂,并将其应用于光催化自芬顿水处理中,提高催化剂的比表面积和孔道结构,增强电荷分离与传输能力和对反应物的吸附能力。

Benefits of technology

It significantly improves the production of H2O2, enhances the adsorption and degradation performance of pollutants, improves the degradation rate and TOC removal rate of pollutants, and the catalyst is simple to prepare and environmentally friendly, avoiding secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116196960B_ABST
    Figure CN116196960B_ABST
Patent Text Reader

Abstract

The present invention relates to a B-doped porous g-C3N4 catalyst, and a preparation method and application thereof, belonging to the technical field of environmental material preparation. Firstly, a catalyst precursor is prepared by simple hydrogen bond self-assembly between boric acid, melamine and cyanuric acid, and then the B-doped porous g-C3N4 is prepared by calcining in a muffle furnace, and then Fe is added to the catalyst precursor. 2+ A photocatalytic self-Fenton system was constructed, and efficient degradation and mineralization of pollutants were achieved under the synergistic effect of OH and photogenerated holes. The B-doped porous g-C3N4 prepared by the present invention simultaneously achieves B doping and morphological regulation, has enhanced charge separation and transport performance and adsorption performance for reactants, and solves the problems of low H2O2 production and insufficient enrichment of pollutants in photocatalytic self-Fenton. A 99.6% degradation rate and a 71.2% total organic carbon (TOC) removal rate of 4-chlorophenol were achieved within 50 minutes, and at the same time, it has good stability, does not produce secondary pollution, and has greatly improved safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a B-doped porous g-C3N4 catalyst, a preparation method and application thereof, and belongs to the technical field of environmental material preparation. Background Art

[0002] With the development of science and technology and society, people's requirements for environmental protection are getting higher and higher. Many factories are unable to continue production due to the fact that the discharged wastewater does not meet the standards. At the same time, the existing water treatment technology is also expensive and may cause secondary pollution. At the same time, it does not have good degradation performance for lower concentration wastewater. Therefore, a technology is needed to achieve deep treatment of wastewater to solve the above problems.

[0003] In recent years, various advanced oxidation processes (AOPs) have been applied to the degradation of pollutants. Among them, the Fenton process is widely used in the degradation of various pollutants because it can produce a large amount of highly oxidizing ·OH. However, it requires the addition of H2O2, which leads to risks in its transportation and storage process. At the same time, a large amount of iron sludge will be generated, which will cause secondary pollution to the environment. These shortcomings have restricted the development of the Fenton process. Therefore, the photocatalytic Fenton technology for the in-situ generation of H2O2 has attracted people's attention. It is achieved by generating H2O2 in situ under light by photocatalysts, and then combining with Fenton reagents to construct a Fenton cycle, thereby efficiently generating ·OH and cooperating with photogenerated holes for the degradation of pollutants. However, there are still two problems in the existing work: (1) The low yield of H2O2 leads to the inability to produce a large amount of ·OH; (2) There is a lack of enrichment of pollutants, and the generated ·OH and photogenerated holes cannot be effectively utilized.

[0004] Among many photocatalysts, g-C3N4 is widely used in the field of photocatalysis because of its suitable band structure, certain light response ability, good stability and easy modification. However, the original g-C3N4 does not have good performance due to its low specific surface area and poor separation and transmission ability of photogenerated carriers. Therefore, it is the key to solve the problem to modify it appropriately to make it meet the requirements of the construction of the photocatalytic self-Fenton system. Summary of the invention

[0005] In view of the defects existing in the prior art, the present invention obtains a B-doped porous g-C3N4 catalyst by calcining after self-assembly of a precursor and applies it to photocatalytic self-Fenton water treatment, so as to solve the problems existing in the prior art in photocatalytic self-Fenton.

[0006] In order to achieve the above purpose, the specific scheme of the present invention is as follows:

[0007] The first object of the present invention is to provide a method for preparing a B-doped porous g-C3N4 catalyst, characterized in that it comprises the following steps:

[0008] S1: Preparation of B-doped porous g-C3N4 precursor: Add boric acid and melamine into ultrapure water and mix well to obtain liquid phase I, add cyanuric acid into ultrapure water and mix well to obtain liquid phase II; mix liquid phase I and liquid phase II, filter, wash, and dry;

[0009] S2: Preparation of B-doped porous g-C3N4 catalyst: calcine, cool and grind the B-doped porous g-C3N4 precursor obtained in step S1 to obtain a B-doped porous g-C3N4 catalyst.

[0010] In one embodiment of the present invention, the calcination in S2 is carried out directly in air;

[0011] In one embodiment of the present invention, the molar ratio of boric acid to melamine is 1:2 to 1:8.

[0012] In one embodiment of the present invention, the ratio of melamine to ultrapure water is 20 mmol: 70-130 mL;

[0013] In one embodiment of the present invention, the ratio of cyanuric acid to ultrapure water is 20 mmol:70-130 mL.

[0014] In one embodiment of the present invention, mixing is achieved by mechanical stirring;

[0015] The stirring time of adding boric acid and melamine into ultrapure water is 30 to 60 minutes;

[0016] The stirring time of adding cyanuric acid to ultrapure water is 30 to 60 minutes;

[0017] The stirring time after mixing liquid phase I and liquid phase II is 100 to 140 minutes.

[0018] In one embodiment of the present invention, the drying temperature is 50-80° C. and the drying time is 6-15 hours.

[0019] In one embodiment of the present invention, the drying temperature is 60°C;

[0020] In one embodiment of the present invention, the drying time is 12h;

[0021] In one embodiment of the present invention, the calcination temperature in step S2 is 520-580°C, the heating rate is 3-6°C / min, and the time is 3-6h;

[0022] In one embodiment of the present invention, the calcination temperature in step S2 is 540-560°C;

[0023] In one embodiment of the present invention, the calcination time in step S2 is 3-5h;

[0024] In one embodiment of the present invention, the heating rate of the calcination step in step S2 is 5°C / min.

[0025] In one embodiment of the present invention, the filtration in step S1 uses an organic polytetrafluoroethylene filter membrane or a nylon 6 filter membrane;

[0026] In one embodiment of the present invention, the pore size of the filter membrane used for filtration in step S1 is 0.22 μm-0.8 μm;

[0027] In one embodiment of the present invention, the filtration in step S1 uses an organic polytetrafluoroethylene filter membrane with a pore size of 0.45 μm.

[0028] The second object of the present invention is to provide a B-doped porous g-C3N4 catalyst.

[0029] The third object of the present invention is to provide a photocatalytic self-Fenton water treatment method using a B-doped porous g-C3N4 catalyst; comprising the following steps:

[0030] The B-doped porous g-C3N4 catalyst was added to the wastewater to be treated, stirred with oxygen to make it saturated with adsorption, and then Fe 2+ A photocatalytic self-Fenton system is constructed as a Fenton reagent, and then it is placed under a light source for irradiation, and oxygen is continuously passed during the reaction.

[0031] In one embodiment of the present invention, Fe 2+ The mass ratio of B-doped porous g-C3N4 catalyst is 1:0.54 to 1:1.6.

[0032] In one embodiment of the present invention, the oxygen supply method is selected from directly supplying oxygen or supplying air;

[0033] In one embodiment of the present invention, the light source is a xenon lamp, a high pressure mercury lamp or sunlight.

[0034] In one embodiment of the present invention, the light source is a xenon lamp with an AM 1.5 filter, and the wavelength range is 300-1100nm.

[0035] In one embodiment of the present invention, the B-doped porous g-C3N4 catalyst can be used to degrade 4-chlorophenol, 2,4-dichlorophenol, bisphenol A, tetracycline, hydroquinone, resorcinol, ciprofloxacin, etc.

[0036] Beneficial effects of the present invention:

[0037] (1) The present invention prepares a photocatalyst precursor through simple hydrogen bond self-assembly between melamine, cyanuric acid and boric acid, and obtains a B-doped porous g-C3N4 catalyst after calcination. At the same time, the doping of B and the regulation of morphology are achieved, so that the photocatalyst has a better electronic configuration, a larger specific surface area and more pore structures, thereby promoting the separation and transmission of charges and the adsorption capacity of reactants.

[0038] (2) The B-doped porous g-C3N4 prepared by the present invention has enhanced H2O2 production performance and enhanced pollutant adsorption and degradation performance. The H2O2 production is about 3 times higher than that of the original g-C3N4, and the production reaches 103μmol / L within 50min. The adsorption performance of pollutants (taking 4-chlorophenol as an example) is enhanced from 6.4mg / g to 16.8mg / g, and the degradation performance is measured by the rate constant k value, from 0.0034min -1 Enhanced to 0.0192min -1 , an increase of 5.7 times.

[0039] (3) The present invention uses a photocatalytic self-Fenton system based on B-doped porous g-C3N4 to efficiently utilize the in-situ generated H2O2 to produce a large amount of ·OH. At the same time, the Fenton cycle is realized under the action of photogenerated electrons, and the photogenerated holes are coordinated to achieve efficient degradation and mineralization of pollutants. After constructing the photocatalytic self-Fenton system, the degradation performance is improved from 0.0192min -1 Enhanced to 0.0957min -1 Compared with the original g-C3N4, the degradation rate of 4-chlorophenol (20ppm) was improved by 28.2 times, and 99.6% of the degradation rate of 4-chlorophenol (20ppm) was achieved within 50 minutes. The TOC removal rate within 50 minutes was also increased from 5.8% of the original g-C3N4 to 71.2%, an increase of 12.3 times. At the same time, compared with the Fenton process, the present invention is more economical and environmentally friendly, the preparation of the catalyst is also relatively simple, and it will not cause secondary pollution to the environment. At the same time, the safety is also greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 are the SEM images and TEM images of the prepared samples, where a and b are the SEM images and TEM images of g-C3N4 prepared in Comparative Example 1, and c and d are the SEM images and TEM images of B-C3N4 prepared in Example 1.

[0041] Figure 2Are the XRD spectra and XPS spectra of the prepared samples, where a is the XRD spectrum of g-C3N4 prepared in Ratio 1, CA-C3N4 prepared in Comparative Example 2, and B-C3N4 prepared in Example 1, and b, c and d are the XPS total spectrum, N 1s fine spectrum and C1s fine spectrum of CA-C3N4 prepared in Comparative Example 2 and B-C3N4 prepared in Example 1, respectively.

[0042] Figure 3 Figure 2 is the adsorption-desorption isotherm diagram and pore size distribution diagram of the prepared samples, a is the adsorption-desorption isotherm diagram of g-C3N4 prepared in Example 1 and B-C3N4 prepared in Example 1, b is the pore size distribution diagram of g-C3N4 prepared in Example 1 and B-C3N4 prepared in Example 1.

[0043] Figure 4 a is the adsorption kinetics diagram of g-C3N4 prepared in Comparative Example 1 and B-C3N4 prepared in Example 1, and b is the O2-TPD diagram of g-C3N4 prepared in Comparative Example 1 and B-C3N4 prepared in Example 1.

[0044] Figure 5 This is a graph of the H2O2 yields of the samples obtained in Examples 1-4 and Comparative Examples 1-2.

[0045] Figure 6 are graphs related to the degradation activities of the prepared samples, wherein a is a degradation curve graph of the samples obtained in Examples 1-4 and Comparative Examples 1-2, b is a photocatalytic self-Fenton (PSF) degradation curve graph of samples with different FeSO4·7H2O addition amounts, c is a bar graph of the k values ​​of the photocatalytic degradation of g-C3N4 prepared in Comparative Example 1, the photocatalytic degradation of B-C3N4 prepared in Example 1, and the photocatalytic self-Fenton degradation of B-C3N4 prepared in Example 1, and a bar graph of the photocatalytic degradation of g-C3N4 prepared in Comparative Example 1, the photocatalytic degradation of B-C3N4 prepared in Example 1, the photocatalytic self-Fenton degradation of B-C3N4 prepared in Example 1, and the TOC removal rate of Fenton, and d is a photocatalytic self-Fenton cycle performance graph of B-C3N4 prepared in Example 1. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with specific implementation examples.

[0047] A specific method for testing the photocatalytic self-Fenton degradation activity of the photocatalyst prepared in the present invention is as follows: 20 mg of the catalyst is added to 50 mL of 4-chlorophenol (4-CP) solution (20 ppm), ultrasonically dispersed to make it uniform, and then stirred for 30 min under the condition of passing O2 to make it adsorbed saturated, 1 mL of the liquid is taken through a 0.45 μm 13 mm nylon syringe filter to remove the catalyst powder, and used for liquid chromatography testing. Then 5 mg of FeSO4·7H2O is added, and the catalyst powder is irradiated under a xenon lamp (AM1.5 filter) under continuous passing O2, and 1 mL of the liquid is taken through a 0.45 μm 13 mm nylon syringe filter every 10 min to remove the catalyst powder, and then the concentration is tested by liquid chromatography; the degradation performance is indexed by the rate constant k value.

[0048] The reaction was completed after 50 minutes of illumination. 3 mL of the clarified filtrate after the reaction was added to 2 mL of potassium titanium oxalate-sulfuric acid solution (potassium titanium oxalate: 7.08 g / L, sulfuric acid: 88.3 g / L), shaken and allowed to stand for 10 minutes, and then placed in a quartz cuvette. The absorbance was detected at 400 nm using an ultraviolet spectrophotometer, and the H2O2 concentration was calculated using the standard curve.

[0049] The concentration of 4-chlorophenol was detected by ultra-high performance liquid chromatography (HPLC) equipped with a Venusil HILIC carbon 18 liquid column (4.6×250 mm, 5 μm). The mobile phase ratio used was chromatographic grade acetonitrile / ultrapure water (v / v) = 55 / 45, the flow rate was 1.00 mL / min, and the ultraviolet detection wavelength was 225 nm. The peak position corresponding to the retention time of about 5 min in the obtained spectrum was the peak position corresponding to 4-CP. The peak area was obtained by integrating the peak, and the concentration of the 4-CP solution with a known concentration could be determined by the peak area.

[0050] The total organic carbon (TOC) concentration was measured by a total organic carbon analyzer, with the concentration before degradation being recorded as C0 and the concentration after degradation being recorded as C. The TOC removal rate was calculated by the following formula: TOC removal rate (%) = [1-(C / C0)]*100%.

[0051] Test method for catalyst adsorption performance: add 20 mg of the prepared catalyst to 50 mL of 4-CP solution (80 ppm), stir continuously with a magnetic stirrer, take 1 mL of liquid every 2 minutes, remove the catalyst powder with a 0.45 μm 13 mm nylon syringe filter, and then test its concentration by liquid chromatography. The reduction amount is the adsorption amount of the catalyst.

[0052] The light source uses a xenon lamp with an AM 1.5 filter, and the wavelength range is 300-1100nm.

[0053] Example 1

[0054] A method for preparing B-doped porous g-C3N4 comprises the following steps:

[0055] (1) Dissolve 20 mmol of melamine and 5 mmol of boric acid in 100 mL of ultrapure water and stir for 45 min, and then dissolve 20 mmol of cyanuric acid in 100 mL of ultrapure water and stir for 45 min, then mix the two and continue stirring for 120 min. Filter with a 0.45 μm organic polytetrafluoroethylene filter membrane and wash with ultrapure water, then dry in a 60 ° C oven for 12 h to obtain a precursor of B-doped porous g-C3N4.

[0056] (2) The precursor of B-doped porous g-C3N4 obtained in step (1) is placed in an alumina crucible, placed in a muffle furnace and heated to 550°C at 5°C / min, calcined for 4 hours, cooled to room temperature and then ground to obtain B-doped porous g-C3N4, recorded as B-C3N4.

[0057] Example 2

[0058] A method for preparing B-doped porous g-C3N4 comprises the following steps:

[0059] (1) Dissolve 20 mmol of melamine and 2.5 mmol of boric acid in 100 mL of ultrapure water and stir for 60 min, and then dissolve 20 mmol of cyanuric acid in 100 mL of ultrapure water and stir for 60 min, then mix the two and continue stirring for 140 min. Filter with a 0.45 μm organic polytetrafluoroethylene filter membrane and wash with ultrapure water, then dry in an oven at 80 ° C for 15 h to obtain a precursor of B-doped porous g-C3N4.

[0060] (2) The precursor of B-doped porous g-C3N4 obtained in step (1) is placed in an alumina crucible, placed in a muffle furnace and heated to 560°C at 6°C / min, calcined for 5 hours, cooled to room temperature and then ground to obtain B-doped porous g-C3N4, recorded as 2.5B-C3N4.

[0061] Example 3

[0062] A method for preparing B-doped porous g-C3N4 comprises the following steps:

[0063] (1) Dissolve 20 mmol of melamine and 7.5 mmol of boric acid in 100 mL of ultrapure water and stir for 50 min, and then dissolve 20 mmol of cyanuric acid in 100 mL of ultrapure water and stir for 50 min, then mix the two and continue stirring for 130 min. Filter with a 0.45 μm organic polytetrafluoroethylene filter membrane and wash with ultrapure water, then dry in a 70 ° C oven for 14 h to obtain a precursor of B-doped porous g-C3N4.

[0064] (2) The precursor of B-doped porous g-C3N4 obtained in step (1) is placed in an alumina crucible, placed in a muffle furnace and heated to 555°C at 5.5°C / min, calcined for 4.5h, cooled to room temperature and then ground to obtain B-doped porous g-C3N4, recorded as 7.5B-C3N4.

[0065] Example 4

[0066] A method for preparing B-doped porous g-C3N4 comprises the following steps:

[0067] (1) Dissolve 20 mmol of melamine and 10 mmol of boric acid in 100 mL of ultrapure water and stir for 35 min, and then dissolve 20 mmol of cyanuric acid in 100 mL of ultrapure water and stir for 35 min, then mix the two and continue stirring for 110 min. Filter with a 0.45 μm organic polytetrafluoroethylene filter membrane and wash with ultrapure water, then dry in a 50 ° C oven for 13 h to obtain a precursor of B-doped porous g-C3N4.

[0068] (2) The precursor of B-doped porous g-C3N4 obtained in step (1) is placed in an alumina crucible, placed in a muffle furnace and heated to 540°C at 4°C / min, calcined for 3.5h, cooled to room temperature and then ground to obtain B-doped porous g-C3N4, recorded as 10B-C3N4.

[0069] Comparative Example 1

[0070] A method for preparing g-C3N4 comprises the following steps:

[0071] Place 5 g of melamine in an alumina crucible, place it in a muffle furnace and heat it to 550°C at 5°C / min, calcine for 4 h, cool to room temperature and then grind to obtain g-C3N4.

[0072] Comparative Example 2

[0073] A method for preparing porous g-C3N4 comprises the following steps:

[0074] (1) Dissolve 20 mmol of melamine and 20 mmol of cyanuric acid in 100 mL of ultrapure water and stir for 45 min, then mix the two and continue stirring for 120 min. Filter with a 0.45 μm organic polytetrafluoroethylene filter membrane and wash with ultrapure water, then dry in a 60 ° C oven for 12 h to obtain a porous g-C3N4 precursor.

[0075] (2) The porous g-C3N4 precursor obtained in step (1) is placed in an alumina crucible, placed in a muffle furnace and heated to 550°C at 5°C / min, calcined for 4 hours, cooled to room temperature and then ground to obtain porous g-C3N4, recorded as CA-C3N4.

[0076] Comparative Example 3:

[0077] Fenton system degradation activity:

[0078] (1) Add 5 mg of FeSO4·7H2O to 50 mL of 4-CP solution (20 ppm), and then place on a stirring table and stir for 30 min.

[0079] (2) 10.3 μmol of H2O2 was added to the above solution to initiate the Fenton reaction. Every 10 min, 1 mL of the liquid was taken out and passed through a 0.45 μm 13 mm nylon syringe filter, and then its concentration was tested by liquid chromatography.

[0080] The degradation activity, H2O2 concentration, TOC removal rate and adsorption performance of Examples 1-4 and Comparative Examples 1-2 were tested respectively; and the degradation activity of Comparative Example 3 was tested.

[0081] Figure 1 From Figures a and b, it can be seen that g-C3N4 presents a thicker sheet stacking structure, which is not conducive to the separation and transmission of charges or the adsorption of reactants, and is also the reason for its poor activity; from Figures c and d, it can be seen that B-C3N4 presents a thin layer of porous sheet structure, which will be more conducive to the adsorption of reactants and the separation and transmission of charges, and it also proves that the present invention achieves the morphology regulation of g-C3N4.

[0082] Figure 2 It can be seen from the XRD spectrum of Figure a that all samples have an in-plane stacking structure of the heptazine unit corresponding to the (100) crystal plane at about 13.1 degrees and an interlayer stacking of the aromatic unit corresponding to the (002) crystal plane at about 27.5 degrees. The two peaks weakened after morphology regulation, indicating the success of morphology regulation. The reduction of in-plane stacking indicates that there is a pore structure in the plane, and the reduction of interlayer stacking indicates its thinner sheet structure. After B doping, the (002) peak shifted from 27.7° to 27.5°, indicating that the interlayer stacking distance between aromatic units increased due to the doping of B. It can be seen from Figure b that after B doping, a new peak is generated at 192eV, which belongs to the NBN peak. Combined with the obvious weakening of the NC=N peak at 288.4eV in Figure d, it indicates that C times B is replaced at NC=N. The area of ​​each peak in Figure c is shifted, which further proves that the doping of B changes its internal electronic structure. The above results prove the successful doping of B and the realization of morphology regulation.

[0083] Figure 3 It can be seen that as B-C3N4 has a larger specific surface area and more pore structures, it will be beneficial to its adsorption of reactants.

[0084] Figure 4 It can be seen that the B-C3N4 prepared in Example 1 has a greatly improved adsorption capacity for 4-CP and O2, which will be more conducive to reducing O2 to H2O2 and degrading 4-CP to harmless products.

[0085] Figure 5 It can be seen that the H2O2 yield of B-C3N4 prepared in Example 1 is 2.92 times that of g-C3N4 prepared in Comparative Example 1, which will be beneficial to the subsequent photocatalytic self-Fenton to produce more ·OH for pollutant degradation. However, the H2O2 yield of CA-C3N4 with only morphology control was not significantly improved, which also illustrates the necessity of combining B doping.

[0086] Figure 6 It can be seen from Figure a that under the optimal B doping ratio, the degradation activity of B-C3N4 prepared in Example 1 is improved from 25% degradation in 50 minutes to 68% degradation compared with g-C3N4 prepared in Comparative Example 1; it can be seen from Figure b that after constructing the photocatalytic self-Fenton, the degradation activity of B-C3N4 prepared in Example 1 is further improved to 99.6% degradation in 50 minutes; it can be seen from Figure c that the k value of the photocatalytic self-Fenton system of B-C3N4 prepared in Example 1 is improved by 28.2 times compared with g-C3N4 prepared in Comparative Example 1, and the TOC removal rate is improved by 12.3 times; and in comparison with the Fenton system, when the amount of H2O2 added is twice the amount produced in situ in the photocatalytic self-Fenton system, the Fenton process has only a TOC removal rate of 27.1%, proving the superiority of the photocatalytic self-Fenton system water treatment method. And from Figure d, it can be seen that even after 4 cycles, the activity of the catalyst has not been greatly reduced, proving that the catalyst has good stability.

[0087] In summary, the present invention realizes the doping and morphology control of B through the self-assembly of the precursor supramolecule in one step, and prepares B-doped porous g-C3N4. The electronic configuration inside g-C3N4 is changed by doping, making it more conducive to the separation and transmission of photogenerated carriers. The specific surface area can be increased by morphology control, which is more conducive to the adsorption of reactants; it has excellent photocatalytic H2O2 production performance and adsorption performance of reactants. The prepared B-doped porous g-C3N4 catalyst has enhanced H2O2 production performance and enhanced adsorption and degradation performance of pollutants. The H2O2 production is increased by about 3 times compared with the original g-C3N4, and the production reaches 103μmol / L within 50min. The adsorption performance of pollutants (taking 4-chlorophenol as an example) is enhanced from 6.4mg / g to 16.8mg / g, and the degradation performance is measured by the rate constant k value, from 0.0034min -1 Enhanced to 0.0192min -1 , which is 5.7 times higher. The photocatalytic self-Fenton system constructed based on B-doped porous g-C3N4 in the present invention produces a large amount of ·OH by efficiently utilizing the H2O2 generated in situ. At the same time, the Fenton cycle is realized under the action of photogenerated electrons, and the synergistic effect with photogenerated holes realizes the efficient degradation and mineralization of pollutants. After constructing the photocatalytic self-Fenton system, the degradation performance is improved from 0.0192min -1 Enhanced to 0.0957min -1 Compared with the original g-C3N4, it was improved by up to 28.2 times, and the degradation rate of 4-chlorophenol (20ppm) was 99.6% within 50 minutes. The TOC removal rate within 50 minutes was also enhanced from 5.8% of the original g-C3N4 to 71.2%, an increase of 12.3 times.

[0088] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A photocatalytic self-Fenton water treatment method, characterized in that: The specific steps are as follows: add the B-doped porous g-C3N4 catalyst to the wastewater to be treated, stir it with oxygen to make it saturated with adsorption, and then add Fe 2+ As a Fenton reagent, a photocatalytic self-Fenton system is constructed, and then it is placed under a light source for irradiation, and oxygen is continuously passed during the reaction; The preparation method of the B-doped porous g-C3N4 catalyst consists of the following steps: S1: Preparation of B-doped porous g-C3N4 precursor: Add boric acid and melamine into ultrapure water and mix well to obtain liquid phase I, add cyanuric acid into ultrapure water and mix well to obtain liquid phase II; mix liquid phase I and liquid phase II, filter, wash, and dry; S2: Preparation of B-doped porous g-C3N4 catalyst: calcining, cooling and grinding the B-doped porous g-C3N4 precursor obtained in step S1 to obtain a B-doped porous g-C3N4 catalyst; In step S1, the molar ratio of boric acid to melamine is 1:2 to 1:

8.

2. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: In step S1, the stirring time of the mixing stage of liquid phase I and liquid phase II is 100-140 min.

3. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: In step S1, the ratio of melamine to ultrapure water is 20 mmol:70-130 mL; the ratio of cyanuric acid to ultrapure water is 20 mmol:70-130 mL.

4. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: The mixing method is mechanical stirring; The stirring time of adding boric acid and melamine into ultrapure water and mixing them evenly is 30 to 60 minutes; The stirring time for the mixing step of adding cyanuric acid to ultrapure water is 30 to 60 minutes.

5. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: In step S1, the drying temperature is 50-80°C and the drying time is 6-15h; In step S1, the filtration is carried out using an organic polytetrafluoroethylene filter membrane or a nylon 6 filter membrane; the pore size of the filter membrane is 0.22 μm-0.8 μm; In step S2, a muffle furnace is used for calcination, the calcination temperature is 520-580° C., the heating rate is 3-6° C. / min, and the calcination time is 3-6 h.

6. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: The Fe 2+ The mass ratio of B-doped porous g-C3N4 catalyst is 1:0.54~1:1.

6.

7. The photocatalytic self-Fenton water treatment method according to claim 1, characterized in that: The oxygen supply method is selected from directly supplying oxygen or supplying air; the light source is a xenon lamp, a high-pressure mercury lamp or sunlight.

8. The photocatalytic self-Fenton water treatment method according to any one of claims 1 to 7, characterized in that: Used to degrade one or more of 4-chlorophenol, 2,4-dichlorophenol, bisphenol A, tetracycline, hydroquinone, resorcinol, and ciprofloxacin.